How Plasmodium falciparum malaria parasites bind to human brain endothelial cells - Claessens, Antoine (The University of Edinburgh, 2011)
Cerebral malaria is characterised by an accumulation of infected erythrocytes in the microvasculature of the brain. Plasmodium falciparum infected erythrocytes have been shown to bind to a Human Brain Endothelial Cell line (HBEC-5i) in vitro. This provides a model for the investigation of interactions between P. falcuparum and human brain endothelium. Currently neither the parasite adhesion ligands on infected erythrocytes, nor the host endothelial cell receptors necessary for this interaction have been identified. In this work, the identity of the host receptor on brain endothelial cells was addressed by binding assays of selected and unselected parasites on a wide range of malaria-associated host molecules. The identity of the parasite ligand was investigated by microarray analysis of parasites after selection for cytoadherence to HBEC-5i. The hypothesis being tested was that the gene encoding the parasite cytoadherence ligand would show significant upregulation in selected compared to unselected paarasites. The P. falciparum laboratory strains 3D7, HB3 and IT/FCR3 were selected for binding to HBEC-5i using a panning assay. Compared to unselected parasites, HBEC-5i selected parasites showed a distinct phenotype with reduced platelet-mediated clumping. There was no significant increase in binding of parasites to any of the known endothelial cytoadherence receptors for P. falciparum after selection on HBEC-5i. Binding inhibition assays with various antibodies and soluble receptors did not greatly block the adhesion of parasites to HBEC-5i except for heparin. Altogether, the receptor(s) mediating the interation with HBEC-5i remains unknown. In order to carry out transcriptional analysis of selected and unselected paarasites form all three parasite strains, it was necessary to update the existing microarray chip which is based on the 3D7 genome. This is because each parasite train has a unique repertoire of variant surface antigens (VSAs) including var, rif and stevor genes. Therefore, to fully analysis HB3 and IT genomes. Unique oligonnucleotide probes were then designed for each new sequence and the 3D7-based microarray chip was updated. Transcriptional analysis was then carried out on selected and unselected parasites of all strains. Microarray data clearly indicated that the most highly upregulated genes after selection were group A or group A-like var genes (HB3var3, 3D7_PFDOO2Oc, ITvar7 and ITvar19), showing 11 to over 100 fold upregulation in selected parasites. The rif gene adjacent to the upregulated var gene was also highly expressed. To a lesser extent some exported proteins like RESA-1, PfEMP3 or PHIST family members also showed increased transcription in HBEC-selected parasites (2-3 fold upregulation). Reverse transcriptase-PCR confirmed the upregulation of group A var genes in selected parasites, suggessted that the group A PfEMP1 variants are major candidate ligands for parasite binding to HBEC-5i. These findings are consistent with previous work showing an association between Group A var genes and cerebral malaria.
Keywords: cerebral malaria; erythrocytes; human brain endothelium; HBEC-5i; parasite ligand; var gene; rif gene; plasmodium falciparum malaria